The 1967 Arab-Israeli War : Origins and Consequences - Louis, Wm Roger; Shlaim, Avi (Cambridge : Cambridge University Press, 2012)
The June 1967 war was a watershed in the history of the modern Middle East. In six days, the Israelis defeated the Egyptian, Syrian and Jordanian armies, seizing large portions of their territories. Two veteran scholars of the Middle East bring together some of the most knowledgeable experts in their fields to reassess the origins and the legacies of the war. Each chapter takes a different perspective from the vantage point of a different participant, those that actually took part in the war and also the world powers that played important roles behind the scenes. Their conclusions make for sober reading. At the heart of the story was the incompetence of the Egyptian leadership and the rivalry between various Arab players who were deeply suspicious of each other's motives. Israel, on the other side, gained a resounding victory for which, despite previous assessments to the contrary, there was no master plan.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Israel-Arab War, 1967